ANALISIS PENGARUH EVA, ROA, DER, VOLUME PERDAGANGAN DAN KAPITALISASI PASAR TERHADAP HARGA SAHAM (Studi Pada Perusahaan Umum Yang Terdaftar Di BEI Tahun 2011-2013) - Raharjo, Ariyo Murti; Haryanto, A. Mulyo (Diponegoro Journal of Management, 2015)
Indonesia Stock Exchange is a transaction trading place of general company in Indonesia. Shares have a market value for the sale and purchase transaction that called the stock price. The stock price is representative of the value of companies that can go up and down. The purpose of this study was to test the stock price which influenced the Economic Value Added (EVA), Return on Assets (ROA), Debt To Equity Ratio (DER), Trading Volume and Market Capitalization in public companies listed on the Stock Exchange during 2011-2013            The population in this study were all general companies listed in Indonesia Stock Exchange and was continuously published financial statements in 2011-2013. Based on a purposive sampling method, samples were obtained by 41 companies in the period 2011-2013, in order to obtain 123 observations. The analysis technique used is multiple linear regression analysis.            The results showed that EVA, ROA, DER, trading volume, and market capitalization simultaneously affect the stock price. Partially trading volume and market capitalization have a significant effect on stock prices. EVA, ROA, and DER has no significant effect on stock prices. And partially EVA, ROA and market capitalization has a positive effect on stock prices. DER, and trading volume has a negative effect on stock prices.